ESR dating of a subfossil shell from Couve Island, Ubatuba, Brazil - Kinoshita, A.; Brunetti, A.; Avelar, WEP; Mantelatto, FLM; Simoes, M. G.; Fransozo, A.; Baffa, O. (Elsevier B.V., 2002)
The occurrence of subfossil material in bottom sediments of Couve Island, Ubatuba region, São Paulo State, is confirmed. The analyzed material consists of a bivalve shell that was dated by the electron spin resonance technique. By the additive irradiation method an archaeological absorbed dose of (25 +/- 5) Gy was obtained and calibration with other dating works in the same area allows the inference of an age of (25 +/- 5) x 10(2) years. The importance of this finding and its paleoecological implications could contribute to elucidating the nature of short-term environmental changes in the Brazilian coastline during the Holocene, as well as becoming an important tool to the understanding of the distribution and biological aspects of the bivalve fauna. (C) 2002 Elsevier B.V. Ltd. All rights reserved.